Clinical Predictors of Wheezing Among Children Infected With Mycoplasma Pneumoniae - Kong, Kaimeng; Ding, Ying; Wu, Beirong; Lu, Min; Gu, Haoxiang (Frontiers in Pediatrics, 2021)
Background: Mycoplasma pneumonia (MP) was not just a common pathogen of respiratory tract infections, but could trigger the exacerbation of asthmatic symptoms in children with or without asthma. Objective: To identify possible risk factors associated with wheezing among children diagnosed with MP infection. Methods: A retrospective analysis of medical records of children aged 28 days to 18 years old who visited the Shanghai Children’s Hospital between January 2019 and January 2020 was carried out, and all children were then classified into three groups: two wheezing groups (with or without MP infection) and a non-wheezing group with MP infection. Information including patient’s demographics, clinical features, laboratory data, and radiography findings was extracted from the electronic medical record system. Chest radiographs were reviewed independently by two board-certified, blinded pediatric radiologists. Results: A total of 1,512 patients were included in our study, and 21.9% of them belonged to the wheezing group without MP infection. Among 1,181 patients with MP infection, 295 people (25.0%) suffered from wheezing, and males accounted for 61%. Through the multivariable logistic regression analyses, we found that six variables were positively associated with wheezing attacks in children with MP infection: male gender (likelihood ratio [LR] = 2.124, 95% confidence interval [CI]: 1.478–3.053), history of allergy (LR= 3.301, 95% CI: 2.206-4.941), history of wheezing (LR = 7.808, 95% CI: 5.276-11.557), autumn in reference to summer (LR = 2.414, 95% CI: 1.500-3.885), non-end-point infiltration in reference to consolidation or pleural effusion (LR = 1.982, 95% CI: 1.348-2.914), and infiltration scope (LR = 1.773, 95% CI: 1.293-2.432). However, the model showed that the probability of wheezing after MP infection decreased as age increased (LR = 0.257, 95% CI: 0.196-0.337). Moreover, the area under the curve (AUC) of the regression model was as high as 0.901 (0.847-0.955). Conclusion: The model integrated with factors including gender, age, season, radiological patterns, infiltration scope, and history of allergy performed well in predicting wheezing attack after MP infection in children.